Extraction of bird blood nuclei and its effect on inhibition of hemolysis (Journal of the College of Basic Education, 2022)
The role of chicken erythrocyte nuclei in inhibiting the lysis of erythrocytes and the permeability test of the blood of some subjects without a disease related to erythrolysis was studied. Saponins and hydrogen peroxide (H2O2) were used as causes for the decomposition of red blood cells outside the body, and the decomposition was observed. Then, the extract of the nuclei of red blood cells was added to chickens, and its role in inhibiting the decomposition was observed. These tests were carried out in five ways, namely:First: Use a sodium chloride solution (0.5%).Second: Use a sodium chloride solution with a hydrogen peroxide solution (0.6%).Third: Use sodium chloride solution with saponin solution (0.12%).Fourth: Use sodium chloride solution with hydrogen peroxide solution and chicken red blood cell nuclei extract.